On the Occurrence of Dangerous Problem Behavior during Functional Analysis: An Evaluation of 30 Applications. Issue 4 (July 2022) - Jessel, Joshua; Rosenthal, Debra; Hanley, Gregory P.; Rymill, Lauren; Boucher, Megan B.; Howard, Monica; Perrin, Jesse; Lemos, Felipe M.
Functional analyses are often conducted by behavior analysts to understand the environmental variables contributing to an individual's problem behavior to better inform treatment implementation. While functional analyses are integral for designing function-based interventions, they often arrange contingencies to evoke and reinforce dangerous problem behavior. In Study 1 we reviewed 22 functional analyses with open-contingency classes including non-dangerous topographies of problem behavior and we found that participants were more likely to exhibit the non-dangerous behavior in 82% of the applications. We then conducted a single-subject comparison of closed and open-contingency classes with four additional participants in Study 2. Our results suggest that the functional analyses with the open-contingency class reduced the likelihood of observing dangerous problem behavior.